2005
DOI: 10.1002/pola.20717
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the luminescent properties and chain length of poly[2‐methoxy‐5‐(2′‐ethyl‐hexyloxy)‐1,4‐phenylene vinylene] on the formation of cis‐vinylene bonds during Gilch polymerization

Abstract: The presence of cis-vinylene bonds in Gilch-polymerized poly[2-methoxy-5-(2 0 -ethyl-hexyloxy)-1,4-phenylene vinylene] is reported. Through fractionation, species with a weight-average molecular weight of less than 37,000 exhibited an abnormal blueshift of photoluminescence spectra in toluene solutions, and this was attributed to the presence of cis-vinylene bonds, as verified by NMR spectroscopy. Surprisingly, the fractionated species ($1 wt %) with a weight-average molecular weight of 5000 were mostly linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It is generally agreed that cis ‐vinylene protons also resonate at δ = 6.5–6.8 ppm for the PPV derivatives prepared by the Wittig reactions 24–26. In our previous study, we have mistakenly attributed the peak at δ = 6.6–6.7 ppm for the MEH‐PPV prepared from monomer I to the formation of cis ‐vinylene bonds during Gilch polymerization 15. As the resulting polymer was subjected to thermal treatment at 200 °C for 1–2 h, half of the methylene bonds were broken as indicated by the decrease of the peak at δ = 6.6–6.7 ppm 16.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is generally agreed that cis ‐vinylene protons also resonate at δ = 6.5–6.8 ppm for the PPV derivatives prepared by the Wittig reactions 24–26. In our previous study, we have mistakenly attributed the peak at δ = 6.6–6.7 ppm for the MEH‐PPV prepared from monomer I to the formation of cis ‐vinylene bonds during Gilch polymerization 15. As the resulting polymer was subjected to thermal treatment at 200 °C for 1–2 h, half of the methylene bonds were broken as indicated by the decrease of the peak at δ = 6.6–6.7 ppm 16.…”
Section: Resultsmentioning
confidence: 96%
“…Lately, we discovered the presence of methylene defects (or bonds) in MEH‐PPV chains—defects that are prone to break at 200 °C, at least 150 °C lower than the major degradation temperature of defect‐free MEH‐PPV. This bond has been mistakenly assigned to the cis defect in our previous studies because of the similarity between their 1 H‐NMR spectra 15. Through thermal annealing of MEH‐PPV in order to break the methylene bonds at 200 °C, the extent of chain aggregation was significantly reduced, so that the maximum quantum yield of photoluminescence (PL) was increased to six times that of untreated MEH‐PPV 16…”
Section: Introductionmentioning
confidence: 97%
“…The molecular weights of these two polymers are markedly different; for poly͑2Ј-methoxy-5-2-ethyl-hexoxy͒-1,4-phenylene vinylene ͑MEH-PPV͒ the upper limit is ϳ300 000 g / mol, while for poly͑2-͑3Ј ,7Ј-dimethyloctyloxy͒-5-methoxy-1,4-phenylenevinylene͒ ͑OC 1 C 10 -PPV͒ the molecular weight can be as high as 1 900 000 which corresponds to ϳ7000 repeat units. 41,42 Dry powder was dissolved under stirring in toluene. For films the concentration was ϳ5 mg/ ml, and films were made by spin coating at 1500 rpm/ 30 s deposition on a glass plate.…”
Section: Methodsmentioning
confidence: 99%
“…The copolymerization of MEH–PPV monomers with DPO–PPV monomers via the Gilch route22 is prone to form an alternative copolymer:23 That is, MEH–PPV monomers prefer to react with DPO–PPV monomers and vice versa. We also found that MEH–PPV molecular chains were easily cleaved from their cis‐linkage defects by a thermal treatment in our previous study 24, 25. Thus, we thought that if MEH–PPV/DPO–PPV polyblends were thermally treated in vacuo , their constituent polymers would be able to react and link with each other and turn the polyblend into a system more like a block copolymer.…”
Section: Introductionmentioning
confidence: 76%